Measuring Family Socioeconomic Position - Gibbings, J; Strazdins, L; Blakemore, T (My University, 2009)
This paper demonstrates and discusses the derivation of a measure of socioeconomic position for Australian families, in particular those participating in Growing Up in Australia: the Longitudinal Study of Australian Children (LSAC). The measure derived followed the methods established for the Canadian National Longitudinal Study of Children and Youth (NLSCY). This paper focussed on the development and application of the measure to the identified dataset and not upon the theoretical underpinnings of socioeconomic position or its measurement. To begin, the article briefly reviews the adopted conceptualisation of socioeconomic position, the importance of socioeconomic position, and how its measurement has been approached.
Keywords: Finance; Income, wealth and finances; Finance; Income, wealth and finance